A Review On Communication Theories And Practices In Health Perspective - Vimala, Govindaraju; Kamalakannan, Kunachagaran (International Journal Documentation & Research Institute (IJDRI), 2021)
Communication in healthcare significant between health care professionals and patients as bridge in clearing miscommunication associated with mistreatment, malpractice and unsatisfactory health outcome. Communication also plays important role in patient-centered care as the health care providers has to concern on the patient's need within health as well as beyond it. There are several studies conducted in healthcare and communication and theories have been applied for better healthcare practices and lead to the development of communication approaches with patients. This article reviews theories of communication that have been applied in healthcare communication perspective when interacting with patients.